Ensaio clínico controlado do uso da terapia fotodinâmica em adolescentes com halitose - Lopes, Rúbia Garcia (2014)
Halitosis is a term used to define the unpleasant breath that may have a systemic or oral origin. Volatile sulfur compounds produced by the Gramnegative bacteria mainly cause the bad breath. Using light - along with by chemical agents or not - is common to induce therapeutic and antimicrobial effects in the photodynamic therapy, and the antimicrobial effect happens only in the areas covered by the dye and irradiated by light. The aim of this study was to evaluate the antimicrobial effect of the photodynamic therapy in adolescent halitosis, analyzing the volatile sulfur compounds concentration, measured by gas chromatography (OralChromaTM). 45 adolescents were assessed and randomly divided (through controlled clinical study) into 3 groups that received different treatments: group 1 treatment with photodynamic therapy applied on the back (dorsum) region and on the middle third of the tongue, group 2 tongue scraper and group 3 treatment with tongue scraper and photodynamic therapy. The halitosis diagnosis was performed before and after the OralChroma treatment. The Kruskal-Wallis test was applied and compared with the Student-Newman-Keuls test. The α = 0.05 significance level was considered for all analysis. After the treatment, there was a statistically significant decline on all groups (p <0.001); however, the photodynamic therapy and tongue scraper treatment proved to be more efficient to fully reduce the hydrogen sulfides (median = 0). This study provides a new option for treating adolescent halitosis with immediate effects without mechanical aggression to the lingual papillae, which is common in the conventional treatment with tongue scrapers.